Research on the model of mandibular alveolar bone defect in rabbits - Nguyen, Thi Thuy Duong; Ngo, Thi Quynh Trang; Nguyen, Mai Anh; Tran, Tan Tai; Nguyen, Thanh Tung (Tạp chí Y Dược Huế, 2024)
Objectives: The purpose of this study was to create an animal model of a mandibular alveolar bone defect without compromising the animal’s well-being. Materials and methods: A total of 24 New Zealand white rabbits underwent surgery to create mandibular alveolar bone defects. The animals were sacrificed at 2, 4, 6, 8, 10, and 12 weeks post-surgery. To assess bone regeneration at the surgical site, radiography, dental cone-beam computed tomography (CT), and histological examination using Hematoxylin and Eosin staining were performed on the skull. Results: A straightforward and easily executable method was devised to create the rabbit mandibular alveolar defect model. After 10 weeks, complete soft tissue and bone regeneration were observed. X-ray and cone-beam CT evaluations demonstrated a progressive increase in bone density from weeks 2 to 12. Histological examination revealed that the alveolar bone structure was formed incrementally at the surgical site. The bone and connective tissue had filled the defect after 8 weeks. Conclusion: The creation of a model of mandibular alveolar bone defects in rabbits is a straightforward process that can be used to assess the regeneration of alveolar bone at the defect site. This animal model can serve as the foundation for tests to evaluate the capacity of biomaterials to regenerate the alveolar bone